PENGARUH HARGA, KUALITAS LAYANAN, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA TOKOPEDIA DI JAKARTA SELATAN - Aditya Pasha Muhammad Natawijaya (2022)
This research model is a quantitative research that aims to determine and prove the effect of Price, Service Quality and Brand Image on Purchase Decisions in e-commerce Tokopedia. This study uses respondent of South Jakarta as a sample and the number of samples used is 100 respondents with the Non-Probability Sampling method with purposive type. The data collection technique uses a questionnaire using the Google Form Platform. The test tool used is Partial Least Square (PLS) as a test tool. The test used in this study is the statistical T test, R test and Q test. The results of smart PLS 3.0 test are (1) there is a positive and significant influence of price on purchasing decision with 0.714 original sample score (2) there is a not significant influence of quality service on purchasing decision with 0.714 original sample score 0.400 (3) there is a not significant influence of brand image on purchasing decision with -267 original sample score